Perilaku Burung Elang (Nisaetus cirrhatus) Mengamankan Sarang: Studi Kasus Di Hutan Pendidikan dan Penelitian Fakultas Kehutanan Universitas Mulawarman Samarinda - Chandradewana Boer; Ridwan Ridwan; Ari Prasetya (ULIN: Jurnal Hutan Tropis, 2021)
This study aims to determine the nest funding and behaviour of Changeable Hawk-eagle (Nisaetus cirrhatus). The research was carried out at the Forest for Education of Forestry Faculty of Mulawarman University. The result showed that the male hawk watched the nest more than female during the breeding season.  Furthermore, drones were used to obtain the position of the eggs due to the high nest tree.